Economical and Structural Feasibility of Concrete Cellular and Solid Blocks in Kurdistan Region - Rostam, Dilan M.; Ali, Taghreed K.M.; Atrushi, Dawood S.S. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2016)
Cellular concrete blocks are the major building materials in Kurdistan Region in Iraq. This study is carried out to check the economical and structural feasibility. The integrity of the blocks as well as its industrial production process compared with local and international standards. Recommendations for the concrete block production have been given in this paper. Samples from 10 local factories of total 60 blocks have been collected and tested at Koya University Laboratory. The carried out tests covered the dimensions, compression strength and water absorption of the samples. The results of this research study were compared with the requirements of the Iraqi and European specifications. They showed that the products of all factories do not fulfil the specified requirements. The dimensions of specimens exhibited relatively high deviations with no recommended tolerances for dimensions of the blocks. The results analysis showed that the weight of the 400x200x200mm block size was about 20-23 kg and the size of the represented voids was about 60% of the volume. This study made some regulatory recommendations to standardise the concrete block production in the region.